Human Rights Due Diligence in Global Business Toward Mandatory International Legal Standards - Danuarta, I Putu Bogi; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pekalongan, 2024)
International business law is undergoing a significant paradigmatic transformation marked by a shift from voluntary Human Rights Due Diligence (HRDD) standards (soft law) toward mandatory regulation (hard law). This transformation signifies a strengthened legal accountability of global corporations for human rights (HR) within increasingly complex transnational supply chains. This study aims to analyze the impact of the transition from soft law to hard law on the effectiveness of corporate compliance with human rights principles and to formulate an ideal international mechanism for the universal harmonization of HRDD. The research employs a normative legal method with a conceptual approach, utilizing primary legal materials such as the United Nations Guiding Principles on Business and Human Rights (UNGPs), the EU Corporate Sustainability Due Diligence Directive (CSDDD), and other relevant international legal instruments. Secondary legal materials include academic literature and empirical studies on HRDD effectiveness, while tertiary materials—such as legal dictionaries and encyclopedias—are used to ensure terminological precision and analytical clarity. The findings reveal that the transition toward mandatory HRDD has enhanced normative legitimacy and broadened corporate accountability frameworks; however, its substantive effectiveness remains constrained by regulatory fragmentation across jurisdictions and limited access to remedies for victims, particularly in developing countries. This research proposes the Global Harmonized HRDD Framework as a conceptual solution that integrates corporate accountability, legal certainty, and substantive justice within a comprehensive and equitable international legal architecture